The study of the road network formation patterns - Санько, Ярослав Володимирович; Ройко, Юрій Ярославович (Technology audit and production reserves, 2013)
Recent researches indicate that the street is no longer an architectural element of urban design, but a universal transport artery. Therefore, when designing streets more attention should be paid to its functional aspect than architectural. However, the limits of the varying of distances between main streets do not allow to optimize the determination of the length of the road network segment. This paper covers the influence of parameters of traffic flows and the number of people on the distance between the main streets while determining the structure of the road network of the rural territory as well as of other functional areas of any settlement. The proposed dependence of the transports calculation definition, which involves the traffic flow structure, allows to study the influence on the optimal length of the road network segment as a separate functional area and as the entire city. In general, the obtained patterns allow to determine the optimal length of the road network segment while the design of new rural territories or determine the parameters of traffic flows and rural development with the existing transportation network.